Portable AEROHUB- UniMAP Fire Fighter - Kamaruddin, Hussin, Brig. Jen. Dato' Prof. Dr.; M. Nasir, Zainal Ariff, Prof.; Shamsul Baharin, Jamaludin, Assoc. Prof. Dr.; Khairul Nizar, Ismail, Dr.; Che Mohd Ruzaidi, Ghazali, Assoc. Prof. Dr.; Omar, Bahari (Malaysian Invention and Design Society (MINDS), 2010)
Brig. Jen. Dato' Prof. Dr. Kamarudin Hussin and his team won bronze for Portable Aerohub - UniMAP Fire Fighter. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.